Chelovek i zakon . Chelovek i zakon . People and the Law . Человек и закон - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of the project of the new Russian Constitution and the problems of privatization; segment on crime in Crimea. Contributors: Karpov, Aleksandr (Anchor); Krauze, IUrii (Anchor) Обсуждение проекта новой российской конституции и проблем приватизации; о преступлениях в Крыму. Создатели: Карпов, Александр (Ведущий/Ведущая); Краузе, Юрий (Ведущий/Ведущая)